1972
DOI: 10.1152/ajplegacy.1972.223.2.268
|View full text |Cite
|
Sign up to set email alerts
|

Temporary alteration of cerebrovascular permeability to plasma protein during drug-induced seizures

Abstract: Temporary alteration of cerebrovascular permeability to plasma protein during drug-induced seizures. Am. J. Physiol. 223(2): 268-277. 1972.-The blood-brain barrier normally restricts the entry of plasma proteins into the central nervous system. Regional increases in the penetration of albumin-1251' into brain were observed in paralyzed, artificially respired animals convulsed for 5, 15, 30, and 60 min with pentylenetetrazol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

1973
1973
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…PKC-dependent signaling events within endothelial cells that lead to increased permeability and barrier dysfunction have been implicated in a number of human diseases, including sepsis, acute lung injury, ARDS, and diabetes (Bannerman and Goldblum, 1999;Idris et al, 2001;SiflingerBirnboim and Johnson, 2003). Electrical or chemical seizure and focal ischemia, which induce verge, also lead to increased vascular permeability (Lorenzo et al, 1972;Sperk et al, 1983). Although the data presented in this study lays the groundwork describing a novel protein involved in modulating vascular permeability, it is important to note that the model used to study verge function thus far is an immortalized brain endothelial cell line and thus may not fully replicate the function of verge in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…PKC-dependent signaling events within endothelial cells that lead to increased permeability and barrier dysfunction have been implicated in a number of human diseases, including sepsis, acute lung injury, ARDS, and diabetes (Bannerman and Goldblum, 1999;Idris et al, 2001;SiflingerBirnboim and Johnson, 2003). Electrical or chemical seizure and focal ischemia, which induce verge, also lead to increased vascular permeability (Lorenzo et al, 1972;Sperk et al, 1983). Although the data presented in this study lays the groundwork describing a novel protein involved in modulating vascular permeability, it is important to note that the model used to study verge function thus far is an immortalized brain endothelial cell line and thus may not fully replicate the function of verge in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…Many observations in epilepsy patients (19)(20)(21)(22)(23)(24), confirmed by animal studies (25)(26)(27)(28), demonstrated that SE provokes transient BBB breakdown and vasogenic edema in the area of the seizure focus. It is commonly proposed that local (relative hypoxia secondary to increased ictal metabolism with an increase in local PCO 2 and lactate) and systemic (increase in blood pressure and decrease in blood pH) physiologic changes induce a vasodilatation, resulting in increased regional blood flow and BBB breakdown (25,26,29).…”
Section: Role Of the Bbb Breakdown In The Genesis Of The Lesionsmentioning
confidence: 86%
“…It is commonly proposed that local (relative hypoxia secondary to increased ictal metabolism with an increase in local PCO 2 and lactate) and systemic (increase in blood pressure and decrease in blood pH) physiologic changes induce a vasodilatation, resulting in increased regional blood flow and BBB breakdown (25,26,29).…”
Section: Role Of the Bbb Breakdown In The Genesis Of The Lesionsmentioning
confidence: 99%
“…30 In the first (seran-polymer) model, the polymer was located in the neuropil, suggesting a leak between endothelial cells. It has been assumed that the intravenously administered albumin-bound dyes which stain the neuropil after topical application of hypertonic solutions do so by passing between endothelial cells.…”
Section: Discussionmentioning
confidence: 99%